2021
DOI: 10.1111/ijcp.14909
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eye care and ocular findings in critically ill COVID‐19 patients

Abstract: Objective The current study aimed to evaluate eyecare needs along with ocular findings in patients treated in intensive care units because of Covid‐19 infection. Materials and Methods A total of 93 patients, 58 men and 35 women, who were under follow‐up and treatment in intensive care because of COVID‐19 infection from 1 January 2021 to 15 February 2021 were included in the study. Detailed eye examinations of the patients were performed with a portable handheld biomicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Included studies reported prevalence of EK between children ( n = 3 studies) (Hartford et al., 2019; Hernandez & Mannis, 1997; Narmawala & Jani, 2017) and adults ( n = 13 studies) (Aggarwal et al., 2022; Araujo et al., 2016; Casillas‐Chavarin et al., 2016; Gok et al., 2021; Hartford et al., 2019; Hernandez & Mannis, 1997; Jammal et al., 2012; Kuruvilla et al., 2015; Li et al., 2008; Mercieca et al., 1999; Narmawala & Jani, 2017; Siebert et al., 2017; Zhang et al., 2022), the main results of the meta‐analysis findings are summarized in Table 3. In individual studies, the prevalence of EK in intensive care patients ranged from 5.9% to 60.0%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies reported prevalence of EK between children ( n = 3 studies) (Hartford et al., 2019; Hernandez & Mannis, 1997; Narmawala & Jani, 2017) and adults ( n = 13 studies) (Aggarwal et al., 2022; Araujo et al., 2016; Casillas‐Chavarin et al., 2016; Gok et al., 2021; Hartford et al., 2019; Hernandez & Mannis, 1997; Jammal et al., 2012; Kuruvilla et al., 2015; Li et al., 2008; Mercieca et al., 1999; Narmawala & Jani, 2017; Siebert et al., 2017; Zhang et al., 2022), the main results of the meta‐analysis findings are summarized in Table 3. In individual studies, the prevalence of EK in intensive care patients ranged from 5.9% to 60.0%.…”
Section: Resultsmentioning
confidence: 99%
“…One study (Imanaka et al, 1997) included both a retrospective and prospective cohort study design, we extracted data from both study designs, so there were 24 sets of data. The frequency of cornel examination in 12 studies (Araujo et al, 2016;Germano et al, 2009;Hartford et al, 2019;Imanaka et al, 1997;Jammal et al, 2012;Kousha et al, 2018;Kuruvilla et al, 2015;Li, 2015;Li, Jin, et al, 2022;Oliveira et al, 2022;Silva et al, 2021;Werli-Alvarenga et al, 2011) is greater than or equal to five times and in the other 10 studies (Casillas-Chavarin et al, 2016;Gok et al, 2021;Hernandez & Mannis, 1997;Li et al, 2008;Martínez-García et al, 2020;Masoudi et al, 2013;Mercieca et al, 1999;Narmawala & Jani, 2017;Oliveira et al, 2022;Siebert et al, 2017) is less than five times during the studies period. Furthermore, the follow-up time in 12 studies (Araujo et al, 2016;Germano et al, 2009;Hartford et al, 2019;Imanaka et al, 1997;Kousha et al, 2018;Kuruvilla et al, 2015;Li, 2015;Li, Jin, et al, 2022;Mercieca et al, 1999;Oliveira et al, 2022;Silva et al, 2021;Werli-Alvarenga et al, 2011) is beyond 7 days and in another three studies (Jammal et al, 2012;…”
Section: Included Studiesmentioning
confidence: 99%
“…Ocular involvement in Covid-19 patients other than conjunctivitis has been described, including keratitis, uveitis, retinal pathologies, and neuro-ophthalmological involvement [ 25 , 32 , 33 ]. These clinical manifestations often occur in patients who required mechanical ventilation and in patients with more severe illness [ 20 , 34 , 35 ]. As our patients who had positive conjunctival swab results and mild symptoms of systemic Covid-19, ocular symptoms were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…Se identificó como asociado al COVID-19 el daño endotelial derivada de la inflamación vascular sistémica o sus manifestaciones tromboembólicas. Además, se detectaron hemorragias retinianas y otro tipo de mancha algodonosa asociadas 12 . Por tanto, como recomendaciones en contextos UCI con pacientes con COVID-19, se evidencia la necesidad de considerar lo siguiente: 13 a. Prevenir es fundamental en UCI.…”
unclassified